Differential expression of the IRF6 gene in the signs of Van der Woude Syndrome: Are distinct genetic modifiers operating? - Rosany de Oliveira Lisboa (University Library System, University of Pittsburgh, 2021)
Objective: The purpose of this study was to report a new variant in the Interferon Regulatory Factor 6 gene (IRF6) and to determine phenotype-genotype correlations in a family segregating Van der Woude syndrome.